Pengaruh Cara Okulasi Terhadap Tingkat Keberhasilan Perbayakan Tanaman Rambutan (Nephelium lappaceum L.) - Pocerattu, Hendry B; Mahulette, Asri S; Makaruku, Marlita Herlin (Universitas Pattimura, 2021)
Rambutan (Nephelium lappaceum L.) is one type of tropical fruit that is in high demand by the public and is one of the leading agricultural commodities in Indonesia. The development of fruits through plant propagation can be done through asexual propagation combined with sexual means as occurs in grafting propagation. The purpose of this study was to obtain data and information on the best grafting method for the success rate of rambutan plant propagation. The research method used a Randomized Block Design (RAK) with a single factor, namely the grafting method consisting of C1 = top opening window grafting, C2 = bottom opening window grafting, C3 = T cover grafting, C4 = closed window grafting. The study consisted of 4 treatments with 4 replications, where each treatment used 10 plants so that in total there were 160 plants. The results showed that the grafting method did not significantly affect all observed variables. The open-top grafting method gave a higher average live grafting for rambutan plant propagation.